Global Governance of Education The Historical and Contemporary Entanglements of UNESCO, the OECD and the World Bank - Elfert, Maren; Ydesen, Christian (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book examines the educational role of three international organizations created as part of the post-World War II multilateral architecture: the United Nations Educational, Scientific and Cultural Organization (UNESCO), the World Bank, and the Organisation for Economic Co-operation and Development (OECD). These organizations have significantly promoted and shaped education as a fundamental feature of the modernization of society and contributed to the globalization of educational norms, policies and technologies. Drawing on primary source materials and interviews, the book provides novel perspectives to the literature on the global governance of education by focusing on the historical entanglements, relations and power struggles between these three organizations, rather than treating them separately. The study sheds light on the homogenizing effects of globalized educational policy-making and the shifting power dynamics in the global governance of education. 'This book makes a very distinctive and important contribution to the literature that critically analyses the influence of the global agencies on education globally; it goes beyond the standard discursive analyses of policy texts to also explore the history of those organisations through archival research and in-depth interviews of the key personnel. What emerges is a powerful analysis which locates those agencies within their historical epochs and shines a light on their tensions and micro-politics, both internally and between organisations.' Paul Morris, Professor of Comparative Education, Institute of Education, University College London, UK. Chapter "UNESCO, the OECD and the World Bank: A Global Governance Perspective" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. .
1.Introduction: Global governance of education and the OECD, UNESCO, World Bank Nexus -- 2. Pre-World War II precursors of the global education governance architecture -- 3. Educational planning in developing countries -- 4. The turbulence of statistics in education -- 5. Lifelong learning: A humanistic counter-perspective -- 6. Revolving doors - Social network analysis of the OECD, UNESCO, World Bank nexus -- 7. Conclusion: The contemporary agendas.
Keywords: Education and state; School management and organization; School administration; Education -- History; International organization; Educational Policy and Politics; Organization and Leadership; History of Education; International Organization